A facile method for the preparation of thermally remendable cross‐linked polyphosphazenes. Issue 5 (18th December 2012) - Cheng, Xinjian; Peng, Cheng; Zhang, Daohong; Liu, Shuzheng; Zhang, Aiqing; Huang, Hui; Lian, Jiansheng
Abstract Novel cross‐linked polyphosphazenes with remendable capacity have been synthesized through the Diels‐Alder reactions. Their structure and properties were characterized by NMR, FT‐IR, GPC, DSC, TGA SEM, and polarizing microscope. The process of Diels‐Alder reaction (D‐A reaction) and retro‐Diels‐Alder reaction (retro‐D‐A reaction) have been investigated by FT‐IR, UV, and DSC. The cross‐linked polyphosphazenes exhibited remendable capability only need a thermal treatment when they were cut by blade, any other treatments such as additional monomer or catalyst, surface treatment or pressure were not needed. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013